PROCESSES OF THE FORMATION OF CIVIL AVIATION IN CENTRAL ASIA IN 1930-1945 - Tukhtabaev Azamjon Sharipkhojaevich (Western European Studies, 2026)
This article analyzes the formation and institutional development of civil aviation in Central Asia during 1930–1945. Using an institutional and historical-comparative approach, the study examines the transformation of aviation from a military-administrative tool into an independent civil transport institution. The research highlights the role of civil aviation in economic modernization, territorial integration, and the enhancement of social mobility in the region. Special attention is paid to the activities of civil aviation during World War II, when it became an integral part of the military-logistical system and ensured the stability of the rear economy. The article concludes that the organizational, кадров, and infrastructural foundations established in this period played a crucial role in the sustainable development of civil aviation in Central Asia in subsequent decades.
Keywords: Central Asia; civil aviation; transport history